AKTIVITAS ANTIOKSIDAN EKSTRAK KULIT BUAH, DAGING BUAH, DAN DAUN APEL SIMANALAGI (MALUS DOMESTICA BORKH. âSIMANA LAGIâ) DENGAN METODE DPPH DAN ABTS - Fitrani Maharani, Dhella
Free radicals are atoms, molecule, or compound that have unpaired electron therefore the atoms are very reactive and unstable. The unpaired electron can interact with electron in other molecules. Negative effects of free radicals can be inhibited by antioxidant which are found in plants such as apple. The objectives of this research were to study antioxidant of activity three parts of simanalagi apple (Malus domestica ??????ÿí??6ð? ?   ãð???±?ã??±±??»?±?í? ?¸ ?± ?±? through of IC50 determination of DPPH (2,2-diphenyl-1-picrylhydrazyl) and IC50 of ABTS (????-azinobis(3-ethylbenzothiazoline-6-sulfonic acid)); determination of total phenolic and total flavonoid; correlation between total phenolic and total flavonoid with IC50 of DPPH and IC50 of ABTS; and correlation between DPPH and ABTS assays. Extraction was conducted by reflux using solvent with increasing polarity, e.g. n-hexane, ethyl acetate, and ethanol. Determination of IC50 of DPPH, IC50 of ABTS, total phenolic, total flavonoid were done using ultraviolet-visible spectrophotometry. Correlation between total phenolic content and flavonoid contents with their IC50 DPPH and IC50 ABTS, and correlation of two antioxidant testing methods ?±?± ®??¸?®?±¸ ??ð?ã /± ?????? method. The highest antioxidant activity by DPPH method and ABTS method was showed by ethanolic flesh extract of simanalagi apple (0.187 ± 0.011 µg/mL and 0.146 ± 0.008 µg/mL, respectively). The highest total phenolic was shown by ethanolic leaves extract of simanalagi apple (13.880 ± 0.066 g GAE/100 g). The highest flavonoid content was given by ethyl acetate leaves extract of simanalagi apple (7.209 ± 0.295 g QE/100 g). Total flavonoid content in all extracts had negative and significant correlation with their IC50 of DPPH and IC50 of ABTS. Total phenolic and flavonoid content in leaves extract of simanalagi apple had negative and significant correlation with their IC50 of DPPH and IC50 of ABTS. IC50 of DPPH of all sample extracts gave positive and significant correlation with their IC50 of ABTS. All parts extracts of simanalagi apple (except n-hexane peel and leaf extracts) were categorized as very strong antioxidant, by DPPH method. Phenolic compounds were the major contributor in antioxidant activities of leaves extracts of simanalagi apple, by DPPH and ABTS methods. Flavonoid compounds gave the major contribution in antioxidant activities of all extracts by DPPH and ABTS methods. DPPH and ABTS methods gave linear results in antioxidant activities of all sample extracts.